X Marks the Spot? A Critique of the Use of Chiasmus in Macro-Structural Analyses of Revelation* - DeSilva, David A. (Journal for the study of the New Testament, 2008)
The role of chiasmus as a structuring device in ancient literature continues to be a much-debated facet of literary and rhetorical analysis, with often overly-exuberant discovery of complex chiasmi spanning whole books running far ahead of the methodological substructure needed to sustain a convincing demonstration of the same. This article analyses three recent attempts to propose a chiastic macro-structural analysis of Revelation and “nds them to present “ne examples of three recurring problems in the quest for the elusive chiasmus: (1) developing chiastic outlines by means of selective shaping of summary statements for major blocks of text; (2) discovering a chiasmus by means of selective reading of key terms; and (3) creation of a chiasmus by means of manipulation of formal markers. The article is offered in the hope that future proposals will take the methodological cautions proposed by critics of chiasmus to heart, as well as the standard rules of critical thinking (e.g., seeking for better alternative structuring devices alongside the quest for the hidden chiasmus).